2020
DOI: 10.11591/ijere.v9i3.20566
|View full text |Cite
|
Sign up to set email alerts
|

How classroom design impacts for student learning comfort: Architect perspective on designing classrooms

Abstract: This study aimed to determine the factors that influence student learning comfort in the classroom and its distribution. This explorative study employed 772 students who were elementary school, junior high school, and senior high school students in several Muhammadiyah Yogyakarta schools. Data collection techniques using open questionnaires. The data analysis technique uses qualitative analysis which consists of three stages: open coding, axial coding, and selective coding. The results showed that the factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Adapun penelitian lainnya menjelaskan bahwa sirkulasi udara, ketenangan, kebersihan, fasilitas yang memadai & mendukung, dan kehadiran teman sebaya menjadi faktor yang paling berpengaruh dalam mewadahi kegiatan belajar yang nyaman [23]. Terlihat bahwa hasil penelitian tersebut juga sejalan dengan penelitian ini.…”
Section: "Luas Meja Yang Lebih Besar Kursi Yang Agak Empuk (Mahasiswa...unclassified
“…Adapun penelitian lainnya menjelaskan bahwa sirkulasi udara, ketenangan, kebersihan, fasilitas yang memadai & mendukung, dan kehadiran teman sebaya menjadi faktor yang paling berpengaruh dalam mewadahi kegiatan belajar yang nyaman [23]. Terlihat bahwa hasil penelitian tersebut juga sejalan dengan penelitian ini.…”
Section: "Luas Meja Yang Lebih Besar Kursi Yang Agak Empuk (Mahasiswa...unclassified
“…Drug abuse among students is a worrying problem that can threaten the survival of nation. Indonesia has required a learning on drugs in the form of formal and nonformal education, seminars and workshops (Agustang & Adam, 2020;Tsoraya et al, 2022;Widiastuti et al, 2020). Not many experts are involved in drugs, because this is a new science whose developments or trends change all the time, so that the development of addictive materials must always be updated (Fraser et al, 2018;Heilig et al, 2021;Seear et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…While we consider educational activities or environments, ergonomics is a key science not only to remove undesired design features from the environment or equipment but also to enhance the educational experience (Zunjic et al, 2015). For evaluating the physical environment of the classroom, several studies have analysed students' physical environment, such as lighting, classroom size, and technology (Guardino and Fullerton, 2010;Hill and Epps, 2009;Ramli, Ahmad, and Masri, 2013;Yang, Becerik-Gerber, and Mino, 2013;Widiastuti, Susilo, and Nurfinaputri, 2020). Yang et al (2013) revealed that students are greatly influenced by spatial qualities, namely visibility and furniture, and ambient attributes, specifically air quality and temperature, both of which are significantly influenced by classroom design, administration, and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (2013) revealed that students are greatly influenced by spatial qualities, namely visibility and furniture, and ambient attributes, specifically air quality and temperature, both of which are significantly influenced by classroom design, administration, and maintenance. Widiastuti et al (2020) stated that the greatest influence on the learning comfort of students comes from the physical conditions in the classroom.…”
Section: Introductionmentioning
confidence: 99%